Women Entrepreneurship and Changing Nature of Livelihood: A Theoretical Analysis - Khanal, Sushila Devi (GS Spark: Journal of Applied Academic Discourse, 2023)
This paper is a review-based synthesis of conceptual and theoretical issues on women entrepreneurship. It connects directly with the development economics and gender studies. The objective of this study is to synthesize conceptual and theoretical reviews on entrepreneurship and livelihood in the particular context of women. This paper is a review paper based primarily on secondary literature and sources of information. The author has applied different theories and approaches to analyze women entrepreneurship and its impact on livelihood. The paper concludes that entrepreneurship development in the context of women and gender studies deserves a wider arena of discourse in conceptual and theoretical dimensions. The study juxtaposes different theoretical ideas with relevant evidence to analyze the impact of women entrepreneurship on livelihood. Women entrepreneurship has a significant impact on livelihood. The study highlights the need for a wider discourse on entrepreneurship development in the context of women and gender studies. The paper provides a framework for further research on women entrepreneurship.